Critical discursive psychology: In and against Psychology - Jasmine, Umme Habiba (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Parker, Ian (2015) Critical discursive psychology. 2nd edition. Houndmills: Palgrave Macmillan (2002). ISBN 978-1-137-48559-5 hbk. Pages xiii + 303 Ian Parker’s book Critical discursive psychology (second edition 2015), comprises texts related to the rise of new critical traditions in psychology along with current debates within the discipline. At the very beginning of the introduction, Ian Parker presents the scope or territory of the content and debatable issues. The book has a polemic aspect in that Parker has invited critical responses to his work, which are included in this volume, to which Parker then also responds. This style is consistent with Parker’s interest to show critical discursive psychology in action, and thus allows readers to understand the ongoing contemporary debates on various topics.